Diagnosis Penyakit Cabai Menggunakan Metode Fuzzy K-Nearest Neighbor (FKNN) - Wildan Gita Akbari; Nurul Hidayat; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Red chili pepper (Capsicum annum l.) is one of the many vegetable commodities consumed by the people of Indonesia, both as a food and flavoring the fulfillment of nutrition. Among commodities, vegetable chilli is vegetables that have the highest economic potential, and the area of pertanaman including the widest chilies among other vegetables (Darmawan and Pasandaran 2000). However, the level of productivity of the chili belongs is still low. Fuzzy K-NN classification is a method that combines technique with fuzzy K-Nearest Neighbor Classifier. Algorithms of Fuzzy K-Nearest Neighbor gives value to the membership class on test data rather than putting test data on a particular class. F-KNN classification is a method used to predict the test data using the value of the degrees of membership test data on each class. The required variable in this study was chilli plant disease symptoms. Highest accuracy of the test results is when K = 5 the value of 92%.